Nonformal Literacy and Bounded Social Transformation: A Historical Study of Kejar Paket A in Indonesia, 1977–1999 - Tarunasena, Tarunasena; Pangestu, Dimas Aldi; Darmawan, Wawan; Restiawati, Hilda; Amin, Syaiful (Journal of Nonformal Education, 2026)
Background – Introduced in 1977, Kejar Paket A provided nonformal literacy for Indonesians who had never entered or completed primary school. This early function is often conflated with the elementary-equivalency pathway developed later.Research Urgency – Existing accounts emphasize policy milestones and aggregate successes while giving insufficient attention to curricular change, delivery mechanisms, documentary bias, and the evidentiary limits of transformation claims.Research Objectives – This study reconstructs Kejar Paket A between 1977 and 1999 and evaluates how its curriculum, learning arrangements, and management mechanisms contributed to literacy, livelihood capability, participation, agency, and educational access.Research Method – Qualitative historical research examined six purposively selected Gita Setra issues published in 1981, 1983, 1986, 1987, 1993, and 1999. Regulations and a contemporary UNESCO study provided corroboration; recent indexed scholarship supported comparison. External and internal criticism assessed provenance, credibility, institutional framing, consistency, and corroboration. Evidence was coded diachronically and thematically and interpreted through contribution analysis.Research Findings – The program developed through foundational literacy, functional consolidation, policy integration, and equivalency-oriented transition. A1–A100 materials combined literacy and numeracy with practical themes, group learning, tutoring, self-study, and low-cost media. Evidence is strongest for access and literacy capability; broader effects cannot be isolated from concurrent change.Research Conclusion – Kejar Paket A provided a flexible bridge among literacy, community learning, and basic education, but its contribution should be expressed as bounded and context-dependent rather than as a singular cause of macro-social change.Research Novelty – The study distinguishes early literacy from later equivalency and integrates source criticism, multidimensional transformation, and explicit evidentiary confidence in one historical account.